Pregnancy Outcomes in Women With Mechanical Prosthetic Heart Valves: A Prospective Descriptive Population-based Study Using the United Kingdom Obstetric Surveillance System (UKOSS) Data Collection System. Issue 2 (June 2018) - Vause, S.; Clarke, B.; Tower, C.L.; Hay, C.; Knight, M.
Abstract : ( BJOG . 2017;124(9):1411–1419) Because pregnancy is considered a thrombogenic state, it is a time of significant risk for women with mechanical prosthetic heart valves (MPHVs). While the number of women with MHPVs becoming pregnant is believed to be on the rise, a lack of good quality data on maternal mortality and complications in this patient population impedes optimal clinical management. This current study was undertaken to determine how many women with MPHVs become pregnant each year in the United Kingdom, the incidence of fetal and maternal complications, and any association between the risk of complications and the type of anticoagulation regimen used.